1997
DOI: 10.1530/eje.0.1370068
|View full text |Cite
|
Sign up to set email alerts
|

Leptin levels are strongly correlated with those of GH-binding protein in prepubertal children

Abstract: Objective: Nutritional status is an important determinant of growth, and previous studies have indicated that this is due, at least in part, to an increased target-tissue sensitivity to GH. An attractive candidate for mediating this effect is leptin, a hormone secreted by the adipose tissue. The aim of this study was to investigate if there was a connection between GH-binding protein (GHBP) and leptin. Design and Methods: We investigated the relationship between serum levels of leptin and those of GHBP in 229 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 41 publications
(41 reference statements)
4
19
0
1
Order By: Relevance
“…However, pair-feeding did not affect serum FFA levels in the transgenic rats. One possible explanation for this result could be that there was no alteration of WAT mass in pair-fed transgenic rats, because it has been shown that circulating FFA concentration is well correlated with adipose tissue mass (15). On the other hand, although hGH treatment reduced fat accumulation in transgenic animals, it did not significantly affect serum FFA levels.…”
Section: Discussionmentioning
confidence: 94%
“…However, pair-feeding did not affect serum FFA levels in the transgenic rats. One possible explanation for this result could be that there was no alteration of WAT mass in pair-fed transgenic rats, because it has been shown that circulating FFA concentration is well correlated with adipose tissue mass (15). On the other hand, although hGH treatment reduced fat accumulation in transgenic animals, it did not significantly affect serum FFA levels.…”
Section: Discussionmentioning
confidence: 94%
“…For example, intracerebroventricular administration of leptin antiserum reduced GH secretion in rats (11) and GH administration to GH-deficient humans has been found to reduce leptin levels, probably through reduced amount of body fat mass (13). Leptin could also influence GH effects in the periphery through association with the GH-binding protein and the IGFBPs (12,33).…”
Section: Discussionmentioning
confidence: 99%
“…In obese individuals, however, high plasma leptin levels do not induce anorexic responses theoretically expected and this inconsistency has led to the concept of leptin resistance Bjarnason et al 1997). In obese GHD human adults, an increased circulating leptin is observed (Bjarnason et al 1997;Fisker et al 1997;Janssen et al 1997), therefore we analysed our obese and GH-deficient hGH transgenic animals to determine whether or not they were leptin-resistant. As mentioned already, the transgenic rats have much increased leptin levels, despite which, food intake is enhanced and locomotor activity suppressed.…”
Section: Leptin Resistancementioning
confidence: 99%